Factors Determining the Choice of Vegetarian vs. Meat-Eating Diets (International Journal of Studies in Nursing, 2019)
Background: There are various opinions of what eating healthy looks like, and it has become a frequent topic of discussion among young adults. Purpose: The purpose of this study was to explore the factors determining the choice of vegetarian vs. meat-eating diet. Method: This study was a qualitative phenomenological study with a descriptive design that was conducted at a college in northern Indiana area using one-on-one interviews. The sample size was 16 individuals, 8 who use the vegetarian diet, and 8 who are meat-eaters. Pender‟s health promotion model was used to guide this study. Results: There were 9 themes that emerged, of which 5 were vegan/vegetarian and 4 were meat-eaters. The vegetarian and vegan themes were limitation of the diet (1), health effects (2), confusion and stigma about diet (3), reasons for choosing this diet (4), and more conscious of what they eat (5). The meat-eating themes were choices (1), health effects (2), mocking and ridiculing (3), and workout (4). Conclusion: Overall, meat-eaters had more choices in their diet and vegetarians and vegans struggled with limitations. They discussed mocking or stigma about their diets as well as health effects. The need for further studies on this topic is evident from the literature review.